Planning Transportation Megaprojects: Paradoxes and Challenges in Planning Complex Projects - Haryo Winarso; Petrus Natalivan Indradjati; Susanti Widiastuti (Journal of Regional and City Planning, 2022)
Transportation megaprojects have become a routine feature in the development of cities and urban infrastructure. The failure of many megaprojects to achieve the desired performance levels is an issue that has been discussed in several studies in recent years, ascribing it to the inability to plan for complexity and uncertainty. This and other problems that are commonplace among megaprojects are yet to be solved despite the employment of highly experienced professionals and resources. The role of the decision-making process in the planning phase is critical in dealing with the complex and uncertain nature of megaprojects. This paper presents a review of literature related to this topic and argues that a major challenge in the planning phase is a cultural misunderstanding of transportation megaprojects, since the rationale behind the development decisions and planning approaches fails to manage complexity and uncertainty. In this study, we identified four paradoxes that occur in transportation megaproject practice that show that top-down and linear planning approaches should be reformed to become more open-minded, nonlinear, and open. Doing so may benefit regional development and broad communities in the future.